A green and efficient technology for the degradation of cellulosic materials: Structure changes and enhanced enzymatic hydrolysis of natural cellulose pretreated by synergistic interaction of mechanical activation and metal salt. (February 2015) - Zhang, Yanjuan; Li, Qian; Su, Jianmei; Lin, Ye; Huang, Zuqiang; Lu, Yinghua; Sun, Guosong; Yang, Mei; Huang, Aimin; Hu, Huayu; Zhu, Yuanqin
Highlights: Mechanical activation and metal salt treatments were combined in a stirring ball mill. Al(NO3 )3 showed better pretreatment effect for cellulose than NaNO3 and Zn(NO3 )2 . Mechanical activation and Al(NO3 )3 treatments showed a synergistic interaction. The presence of Al(NO3 )3 remarkably enhanced the enzymatic hydrolysis of cellulose. A simple, efficient and green technology for the degradation of cellulosic materials. Abstract: A new technology for the pretreatment of natural cellulose was developed, which combined mechanical activation (MA) and metal salt treatments in a stirring ball mill. Different valent metal nitrates were used to investigate the changes in degree of polymerization (DP) and crystallinity index (CrI) of cellulose after MA + metal salt (MAMS) pretreatment, and Al(NO3 )3 showed better pretreatment effect than NaNO3 and Zn(NO3 )2 . The destruction of morphological structure of cellulose was mainly resulted from intense ball milling, and the comparative studies on the changes of DP and crystal structure of MA and MA + Al(NO3 )3 pretreated cellulose samples showed a synergistic interaction of MA and Al(NO3 )3 treatments with more effective changes of structural characteristics of MA + Al(NO3 )3 pretreated cellulose and substantial increase of reducing sugar yield in enzymatic hydrolysis of cellulose. In addition, the results indicated that the presence of Al(NO3 )3 had significant enhancement for the enzymatic hydrolysis of cellulose.